Learning and academic performance styles in nursing internships of a peruvian public university: Estilos de aprendizaje y rendimiento académico en internos de enfermería de una universidad nacional del Perú - Chambi-Choque, Ana Maria (2019)
Objective: To evaluate the learning style (EEAA) and its relation with the academic performance (RA), in Nursing Interns of a national university of Peru. Methods: Cross-sectional, quantitative, correlational study; conducted in 70 nursing interns during 2018, the Honey-Alonso validated questionnaire (CHAEA) was applied for learning styles and record of grades for academic performance, the data were submitted to descriptive and inferential statistics, using SPSS 26.0. Results: The population characteristics, according to age, 84.5% were between 20 and 25 years old, usually single, do not work, although a significant group does, and 82.9% women. In EEAA reflexive learning (0.80) predominates, followed by theoretical (0.75), pragmatic (0.66) and active (0.57). The weight average of R.A. It was 15.84, with a good and excellent qualification, 62.86% presented a good performance, followed by 32.86% with excellent performance. The results of association between EEAA and RA were not significant (P> 0.05). Conclusion: The academic performance of nursing interns was mainly good and excellent. The EEAA evaluation showed the reflexive style as predominant. We found no significant association between learning styles and their contribution to academic performance.